Manajemen BUMDES Mutiara Welirang Dalam Pengelolaan Usaha Air Minum (BPAM) Di Desa Ketapanrame - Wustoto, Karinda; Sukmana, Hendra (LP2M, 2024)
The following research study aims to analyze the Management of Mutiara Welirang BUMDes in the Management of Drinking Water Business (BPAM) in Ketapanrame Village. In the study, a qualitative descriptive research method was used with data collection techniques through observation, interviews, and documentation. This data analysis technique uses the Miles and Huberman (1984) model, including data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that there are findings, namely First, planning, the success proven by BUMDes management in managing the water business with several plans every year such as adding water networks, distributing water to villas in the Trawas area in 2023. Second, the organizational structure formed by BUMDes and the local village government shows success in resource management and the economy at the village level. Third, the direction of BUMDes as a driving force for the establishment of businesses in Ketapanrame Village, communication is carried out well. This has an impact on the success achieved by business units in Ketapanrame, as evidenced by the establishment of the drinking water business unit built another unit and currently there are five business units in the village. Fourth, the coordination of BUMDes Mutiara Welirang shows the success of the planning that has been realized in the distribution of drinking water with net income in 2023 of around Rp. 1,474,452,850. It can be seen that this study shows that the management of BUMDes has achieved success and success in its management according to the vision and mission. However, there are plans for drinking water business units that have not yet been realized related to bottled drinking water because according to BPOM's permit, it has not fulfilled the procedures for product marketing permits.